2012
DOI: 10.2174/156720512799015073
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Physiology Underlying the Rapid Clinical Effects of Perispinal Etanercept in Alzheimers Disease

Abstract: Excess tumor necrosis factor (TNF) plays a pivotal role in the pathogenesis of Alzheimer's disease(AD). Clinical improvement following perispinal administration of etanercept in patients with Alzheimer's disease and other forms of dementia and brain dysfunction is characteristically evident within minutes. The rapidity and constellation of the clinical effects across multiple domains (cognition, mood, memory, motor function, and attention) suggest they are mediated by non-synaptic signaling mechanisms previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 147 publications
(302 reference statements)
1
39
0
Order By: Relevance
“…Adalimumab, a monoclonal anti-TNF-α antibody has been found to improve full scale, verbal and performance IQ in an observational study of 15 patients with rheumatoid arthritis (Raftery et al, 2012). Efficacy of another TNF-α inhibitoretanercept has been studied in Alzheimer's disease (Tobinick, 2012); however, a recent placebocontrolled, double-blind, phase 2 trial of subcutaneous etanercept demonstrated no significant changes in cognition, behaviour and global functioning (Butchart et al, 2015). Preclinical evidence also indicates that toclizumab, which is a monoclonal antibody inhibiting IL-6 signalling, might improve spatial memory and learning in Alzheimer's disease animal model (Elcioglu et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Adalimumab, a monoclonal anti-TNF-α antibody has been found to improve full scale, verbal and performance IQ in an observational study of 15 patients with rheumatoid arthritis (Raftery et al, 2012). Efficacy of another TNF-α inhibitoretanercept has been studied in Alzheimer's disease (Tobinick, 2012); however, a recent placebocontrolled, double-blind, phase 2 trial of subcutaneous etanercept demonstrated no significant changes in cognition, behaviour and global functioning (Butchart et al, 2015). Preclinical evidence also indicates that toclizumab, which is a monoclonal antibody inhibiting IL-6 signalling, might improve spatial memory and learning in Alzheimer's disease animal model (Elcioglu et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Uysal et al (1997) showed that insulin resistance did not develop in obese mice lacking TNF function. Seven years later a series of patient studies began to TNF CAUSES INSULIN RESISTANCE: IMPLICATIONS FOR AD appear in which commercial anti-TNF biological agents reduced insulin resistance in T2DM (Yazdani-Biuki et al, 2004), rheumatoid arthritis [in some (Kiortsis et al, 2005;Gonzalez-Gay et al, 2006, 2012 but not all (Ferraz-Amaro et al, 2011) reports], and ankylosing spondylitis (Kiortsis et al, 2005). In addition, infliximab, one of these commercial anti-TNF biological agents, was tested in obese diabetic mice, and it improved insulin signal transduction in muscle, liver, and hypothalamus.…”
Section: Tumor Necrosis Factor and Insulin Resistancementioning
confidence: 99%
“…Because the intracerebroventricular route is a precarious one, unsuited to regular administration to the same patient, a number of ways to circumvent this problem are being developed to widen the use of these highly successful biological agents to a new patient group. The earliest of these is a novel approach termed the perispinal route (Tobinick et al, 2006(Tobinick et al, , 2010(Tobinick et al, , 2012. Its logic depends on 1) a short period of head-down tilting to gain a gravitational advantage, 2) an awareness of anatomy of Batson's plexus [a valveless venous system that surrounds the spinal column in continuum with the choroid plexus (Nathoo et al, 2011)], and 3) knowledge of the effect of acute hypertension on choroid plexus permeability [a 30-fold increase in albumin in CSF within 10 min of pharmacologically induced acute local hypertension (Murphy and Johanson, 1985)].…”
Section: A Specific Inhibition Of Tumor Necrosis Factormentioning
confidence: 99%
“…The anatomy and physiology of the cerebrospinal venous system, a unique, bi-directional vascular pathway, remains little known in the general medical community, despite recognition in multiple neurosurgical and anatomical publications [18–30]. Trendelenburg positioning may facilitate selective delivery of etanercept into the brain after it reaches the cerebrospinal venous system [10, 3135]. The cerebrospinal venous system provides a direct vascular pathway to the brain (Figs.…”
Section: Introductionmentioning
confidence: 99%